Blockchain-Based Green Waqf and Wakif Trust: A Perception-Based Study of Wakif in Indonesia - Tegar Arif Saputra; Lisa Mursilawati; Agus Dwiyanto; Diah Ayu Setianingrum (UIN Raden Mas Said Surakarta, 2026)
This research was motivated by the suboptimal implementation of green waqf in Indonesia, despite the enormous potential of national cash waqf and the ability of blockchain technology to offer transparency, traceability, and accountability in fund management. The main issue lies not only in the availability of technology, but also in how technology can strengthen wakif trust. This study aimed to analyse the influence of transparency, transaction traceability, data security, reporting accountability, ease of use, and sharia compliance on wakif trust in blockchain-based green waqf management. This study employed a mixed-methods approach with an explanatory sequential design. Quantitative data were collected through questionnaires from 132 respondents recruited through social media, communities, and digital donation users, and were analysed using descriptive statistics, Pearson correlation, and multiple linear regression. Qualitative data were obtained through interviews with 15 informants and analysed thematically. The results show that reporting accountability, sharia compliance, and transparency have a significant effect on wakif trust, while transaction traceability has a marginal effect. Data security and ease of use have no significant effect. Qualitative findings confirm that wakif prioritize the legality of nazhir, clarity of contracts, reporting on fund utilization, and evidence of ecological impact. This study contributes to the literature on digital waqf and Islamic social finance by shifting the discussion from technology adoption to trust-based, sharia-compliant, and impact-oriented governance in blockchain-enabled waqf management. This study concludes that wakif trust is normative-institutional, not merely technological. Consequently, the development of blockchain-based green waqf needs to be directed toward transparent, accountable, sharia-compliant, and impact-oriented governance.